Aspek Bioekologi Gurami Kulit Ular (Trichopodus pectoralis) di Perairan Rawa Banjir Sungai Bilah, Kabupaten Labuhanbatu - Fitriyani Sinaga; Rivo Hasper Dimenta (Universitas Muhammadiyah Prof. Dr. Hamka, 2022)
Background: The potential fish resources of snakeskin gourami (Trichopodus pectoralis) in the flooded swamp waters of Bilah river, Labuhanbatu Regency, are pretty high. Thus, this is one of the essential resources and has economic value. This study aimed to inform the bioecological aspects of snakeskin gourami fish (T. pectoralis). Methods: The determination of 3 sampling points was done using the purposive random sampling method. The sampling of T. pectoralis was carried out using the trap. The data analysis presented information on the abundance of Gonad Maturity Level, growth pattern, the Fulton (K) factor condition, and the Pearson correlation among environment parameters to the T. pectoralis population, which was presented quantitatively. Results: The results showed the length-weight relationship of T. pectoralis in the allometric category. The average relative weight (Wr) for male T. pectoralis was 100.46 ± 8.37, and for females was 99.83 ± 2.30. The mean value of the Fulton’s (K) factor condition in male T. pectoralis (8.94 ± 0.54) and female T. pectoralis (9.27 ± 0.67). Conclusions: T. pectoralis showed an allometric category and domination of the first gonadal maturity level. It describes that the female is abundant in optimum condition and ensures for future generations, and Pearson’s correlation result informs that increasing the value of environmental parameters will affect the optimization of T. pectoralis life.